Evaluating the feasibility of water sharing as a drought risk management tool for irrigated agriculture - Chengot, Rishma; Knox, Jerry W.; Holman, Ian P. (MDPI, 2021)
Droughts can exert significant pressure on regional water resources resulting in abstraction constraints for irrigated agriculture with consequences for productivity and revenue. While water trading can support more efficient water allocation, high transactional costs and delays in approvals often restrict its wider uptake among users. Collaborative water sharing is an alternative approach to formal water trading that has received much less regulatory and industry attention. This study assessed how the potential benefits of water sharing to reduce water resources risks in agriculture are affected by both drought severity and the spatial scale of water-sharing agreements. The research focused on an intensively farmed lowland catchment in Eastern England, a known hot-spot for irrigation intensity and recurrent abstraction pressures. The benefits of water sharing were modelled at four spatial scales: (i) individual licence (with no water sharing), (ii) tributary water sharing among small farmer groups (iii) sub-catchment and (iv) catchment scale. The benefits of water sharing were evaluated based on the modelled reductions in the probability of an irrigation deficit occurring (reducing drought risks) and reduced licensed ‘headroom’ (spare capacity redeployed for more equitable allocation). The potential benefits of water sharing were found to increase with scale, but its impact was limited at high levels of drought severity due to regulatory drought management controls. The broader implications for water sharing to mitigate drought impacts, the barriers to wider uptake and the environmental consequences are discussed
Keywords: water resources; irrigation deficit; farm management; catchment